Analysis of the efficiency of the geographical distribution of secondary education services in the district of Hilla for the academic year (2020-2021) - Jaaz Nasser Al-Fatlawy, Hussein; Fuleih, Lamia (Journal of College of Education, 2022)
SummaryThe research dealt with showing the efficiency of the distribution of secondary education services in the district of Al-Hilla for the academic year (2020-2021) and indicating its impact on the population (2021) and the use of scientific methods represented by arithmetic operations and graphic forms and comparing them with the indicators approved in the Iraqi Ministry of Planning, as the results of the research showed a shortage and deficit in some educational indicators and their discrepancy between the administrative units of the district of Hilla, and the quantitative change in the distribution of secondary education services according to the administrative units for the year (2020) marked a change in the study area, as the highest numbers of secondary education services were recorded in the center of Hilla district for the academic year (2020-2021), as the number of the district’s population for the year (2020) reached (1387470) people, which was characterized by variation and fluctuation between the administrative units of the study area, as well as The results of the research showed that secondary educational services have a correlation with the size and growth of the population and in the light of the results and suggestions.